A New Detection of the Invasive Mexican Rice Borer (Lepidoptera: Crambidae) From Georgia in the United States Based on Morphological and Molecular Data. Issue 1 (23rd May 2022) - Kang, Ilgoo; Wilson, Blake; Carter, Blake; Diaz, Rodrigo
Abstract: The Mexican rice borer, Eoreuma loftini (Dyar), is an invasive herbivore that attacks many gramineous host plants. The species is an economic pest of several grass crops in North America including sugarcane ( Saccharum spp.), rice ( Oryza sativa ), corn ( Zea mays ), and sorghum ( Sorghum bicolor ). The species was first detected in the United States in 1980 and has since expanded its range eastward along the Gulf Coast reaching Louisiana in 2008. A disjointed introduction was detected in Florida in 2012, though range expansion of this population within the state has been limited. Most recently, a separate introduction was detected along the Atlantic coast of Georgia near the South Carolina border (32.19884° N, 81.35894° W). Larvae were collected from sugarcane in 2020 and 2021 and identified as E. loftini . The identification was confirmed with genetic analysis showing >99% similarity with most mitochondrial cytochrome c oxidase subunit 1 (COI) sequences of known E. loftini . This is the furthest north and east of any established population in North America. Potential routes of introduction and impacts to crop production along the U.S. Atlantic Coast are discussed.